2022
DOI: 10.3389/fimmu.2022.1072720
|View full text |Cite
|
Sign up to set email alerts
|

Elevated inflammatory fecal immune factors in men who have sex with men with HIV associate with microbiome composition and gut barrier function

Abstract: IntroductionPeople living with HIV infection (PLWH) exhibit elevated levels of gastrointestinal inflammation. Potential causes of this inflammation include HIV infection and associated immune dysfunction, sexual behaviors among men who have sex with men (MSM) and gut microbiome composition.MethodsTo better understand the etiology of gastrointestinal inflammation we examined levels of 28 fecal soluble immune factors (sIFs) and the fecal microbiome in well-defined cohorts of HIV seronegative MSM (MSM-SN), MSM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Moreover, our results prompted that MSM behavior could alter human immunity response through gut microbiome dysbiosis, this might be the potential mechanism of T-cell phenotype alteration and bioenergy metabolism disorder in the MSM population ( Kruize et al., 2020 ). A recent study demonstrated that gut microbiome in MSM was associated with elevated inflammatory factors, which also supported our conclusion ( Littlefield et al., 2022 ). Different from meta-analysis, our study systematically retrieved HIV and MSM-associated gut microbiome changes from available studies and focused on the influence of these gut microbiomes on human immunity by bioinformatic technology.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our results prompted that MSM behavior could alter human immunity response through gut microbiome dysbiosis, this might be the potential mechanism of T-cell phenotype alteration and bioenergy metabolism disorder in the MSM population ( Kruize et al., 2020 ). A recent study demonstrated that gut microbiome in MSM was associated with elevated inflammatory factors, which also supported our conclusion ( Littlefield et al., 2022 ). Different from meta-analysis, our study systematically retrieved HIV and MSM-associated gut microbiome changes from available studies and focused on the influence of these gut microbiomes on human immunity by bioinformatic technology.…”
Section: Discussionsupporting
confidence: 91%
“…Subgroups with elevated fecal calprotectin levels included women with third-trimester CD4+ T-lymphocyte counts <350 cells/µL consistent with findings from previous studies ( 35 , 36 ). Other studies in HIV-infected individuals described similar ( 37 , 38 ) or elevated fecal calprotectin levels ( 8 , 9 ), most likely depending on the degree of gut mucosal damage and immune dysfunction despite taking cART ( 39 ). In our study, above normal median fecal calprotectin levels were observed in HIV-infected cART-experienced individuals, in agreement with studies in cART-naïve Italians ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 91%
“…The fecal calprotectin levels are thus a useful marker of gut inflammation and an indirect marker of intestinal permeability ( 7 ). Faecal calprotectin levels have been reported to be higher in the HIV-infected population even if on cART compared with that in HIV-uninfected peers ( 8 , 9 ). Despite these studies, the influence of gut inflammation on microbial translocation and systemic inflammation is still insufficiently understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that gut microbiome of MSM is altered independently of HIV-1 infection status, showing higher levels of gastrointestinal in ammation 29 and contributing to an increased risk of HIV-1 infection 30 . On the other hand, Prevotella enriched enterotype in other populations has shown contradictory health effects being related to anti-in ammatory effects of diet 31 and lower risk of infection and mortality in critical care patients 32 but also to different in ammatory conditions 33,34 .…”
Section: Discussionmentioning
confidence: 99%